PENGARUH PERSONAL SELLING TERHADAP PENCAPAIAN TARGET PENJUALAN PRODUK JASA ASURANSI (Kasus pada PT. Prudential Life Assurance Pekanbaru) - Teguh Afridawanto; Meyzi Herianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this study was to determine the effect on the achievement of personal selling insurance product sales at PT. Prudential Life Insurance Pekanbaru. In this study, personal selling was as an independent variable (X) and the achievement of sales targets was as the dependent variable (Y). The samples used were 86 respondents with a sampling technique by using accidental sampling technique.Overall, the data was obtained through questionnaires and further processed for statistical analysis tested as a simple linear regression analysis, t-test, correlation coefficient, and the coefficient of determination by using SPSS 16 for windows. From the calculation results of regression was obtained the correlation coefficient (r) of 0.711, where the value of the correlation coefficient indicates a strong and positive relationship between personal selling (variable x) to the achievement of sales targets (variable y). While the coefficient of determination (R-square) of 0.505, means that personal selling gives strong and significant influence on the achievement of sales target that is equal to 50.5%. The results of hypothesis test (t test) shows that the t value is greater than the table is 9.260 > 1.989, means that personal selling is positive and significant impact on the achievement of sales targets.Keywords: personal selling, sales target achievement, Prudential Life Insurance